The Relationship Between the Mental Revolution and Legal Products in Jokowi's First Term - Musmulyadin Musmulyadin (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Jokowi's big vision regarding mental revolution has a historical background in the era of President Ir. Sukarno. The structuring of the nation's mentality has had a correlation in the past with the development of the nation's character (nation and character building). Jokowi personally has shown practice and discipline in serving the community. However, is Jokowi's behavior automatically followed by state/bureaucratic administrators? Continuity between Jokowi's behavior and bureaucratic behavior that must be implemented as a part of providing services to the community. Jokowi as the holder of the people's mandate through elections must be able to present a legal basis in ensuring the implementation of the vision, mission and action program. The research method used is qualitative with a legal/legal approach, an ethical approach and a hermeneutical approach to related legal texts. The mental revolution has become a national movement with the presence of "Presidential Instruction Number 12 of 2016 concerning the National Movement for Mental Revolution". Then "Regulation of the President of the Republic of Indonesia Number 7 of 2015 concerning Organization of State Ministries". All efforts are expected to have implications for changes in mentality both within the bureaucracy and society. The Jokowi regime's perspective on various national problems that must be restored by strengthening ideology and utilizing technology. Technology has a role in changing the service base from manual to digital. . Jokowi's government through GNRM is expected to be more adaptive and communicative towards society. The bureaucracy must change, but the community must be involved, not just being a tool to justify the actions of the authorities. The mental revolution that has become the reference for the Jokowi government has been successfully presented in various forms of legal regulations. Government officials and law enforcers must take a pedagogic role. The substance of the law makes people aware that upholding the law does not require law enforcement to impose sanctions. Precisely when people are aware that the law is successful. The regime must speak and take a role, not just judge that this can have an electoral impact and forget morals. Therefore, the constitution has provided a mandate to educate the life of the nation. Any regime cannot be separated from the mandate of the constitution, don't let citizens not get intelligence. The mental revolution will only have relevance if society is aware of the law.